Comparative Effectiveness of Left Atrial Appendage Occlusion Versus Oral Anticoagulation by Sex. Issue 7 (14th February 2023) - Zeitler, Emily P.; Kearing, Stephen; Coylewright, Megan; Nair, Devi; Hsu, Jonathan C.; Darden, Douglas; O'Malley, A. James; Russo, Andrea M.; Al-Khatib, Sana M.
Abstract : Background: The comparative real-world outcomes of older patients with atrial fibrillation (AF) treated with anticoagulation compared with left atrial appendage occlusion (LAAO) may be different from those in clinical trials because of differences in anticoagulation strategies and patient demographics, including a greater proportion of women. We sought to compare real-world outcomes between older patients with AF treated with anticoagulation and those treated with LAAO by sex. Methods: Using Medicare claims data from 2015 to 2019, we identified LAAO-eligible beneficiaries and divided them into sex subgroups. Patients receiving LAAO were matched 1:1 to those receiving anticoagulation alone through propensity score matching. The risks of mortality, stroke or systemic embolism, and bleeding were compared between matched groups with adjustment for potential confounding characteristics in Cox proportional hazards models. Results: Among women, 4085 LAAO recipients were matched 1:1 to those receiving anticoagulation; among men, 5378 LAAO recipients were similarly matched. LAAO was associated with a significant reduction in the risk of mortality for women and men (hazard ratio [HR], 0.509 [95% CI, 0.447–0.580]; and HR, 0.541 [95% CI, 0.487–0.601], respectively; P <0.0001), with a similar finding for stroke or systemic embolism (HR, 0.655 [95% CI, 0.555–0.772]; and HR, 0.649 [95% CI, 0.552–0.762], respectively; P <0.0001). Bleeding risk was significantly greater in LAAO recipients early after implantation but lower after the 6-week periprocedural period for women and men (HR, 0.772 [95% CI, 0.676–0.882]; and HR, 0.881 [95% CI, 0.784–0.989], respectively; P <0.05). Conclusions: In a real-world population of older Medicare beneficiaries with AF, compared with anticoagulation, LAAO was associated with a reduction in the risk of death, stroke, and long-term bleeding among women and men. These findings should be incorporated into shared decision-making with patients considering strategies for reduction in AF-related stroke.